CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

Add: 2x(z-x-y)and2y(z-y-x)


Open in App
Solution

To add : 2x(z-x-y)and2y(z-y-x)

Firstly we will multiply the common term with the brackets given, and then add the like terms with one another, we have

=2x(zxy)+2y(zyx)=(2x×z)(2x×x)(2x×y)+(2y×z)(2y×y)(2y×x)=2xz2x22xy+2yz2y22yx=2xz4xy+2yz2x22y2

Hence, On adding 2x(z-x-y)and2y(z-y-x) , we get 2xz-4xy+2yz-2x2-2y2.


flag
Suggest Corrections
thumbs-up
10
BNAT
mid-banner-image